Thermal performance of green roof at Dhaka City in Bangladesh - Rashid, Rumana (2012)
Sustainability development is one of the main issues today around the world. Appropriate use of building design strategy of construction process contributes to reducing the consumption of building energy. Green roof can play a positive role to reduction of roof surface temperature and air temperature that can be translated into energy saving means. The aim of research is to investigate the thermal performance of the green roof and the changes that occurs in the indoor thermal environment with diurnal variation of the room during summer and winter season in subtropical Bangladesh and tropical Malaysia. This research was conducted through field measurement. The pilot study was conducted in Malaysia for two weeks before the main field study was done in Bangladesh for duration of one year. The main reason of the pilot study was to clarify the instrumentation. The pilot study results indicated that the green roof is more effective than bare roof in tropical climate. The pilot study suggested a good potential of similar green roof strategy for Bangladesh. To evaluate thermal performance of green roof in Bangladesh, some quantitative data analysis is necessary before largescale implementation of green roof can be introduced. To meet these requirements, field measurements were carried out locally on selected buildings in Dhaka city. Three building were selected for field study, two buildings with green roof and another was a reinforce cement concrete (R.C.C.) bare roof. A set of thermal data loggers were installed to record the air temperature of indoor, outdoor and surface temperature. Data collection was carried out for duration of two months in winter and five months in summer. Thermal performance evaluation was done by comparative study between green roof and typical concrete bare roof. This research also evaluates U-value and RTTV calculation of different types of green roof and bare roof. The research found that green roof on contemporary building has better thermal performance and comfortable compare to bare roof in summer season. During winter, occasionally green roof reduces the indoor temperature to below comfort zone. It also noted that the thermal performance of green roof depends on the different type of design strategy. Constructed sunken, raised, exposed and organized pot plants green roofs can reduce indoor air temperature to 3.67°C, 1.22°C, 2.49°C and 6.8°C compare to outdoor air temperature. Green roofs also achieve a remarkable surface temperature reduction around 27.63°C. As part of an integrated system of green roof, denser plants can offer a better evaporative cooling impact to the micro-climate. This research suggests that the rooftop garden is one of the natural ecological solutions for reducing the effect of Urban Heat Island (UHI). This study concludes that the use of green roof on contemporary buildings of Bangladesh have significant impact on the overall indoor thermal performance. Thus, contemporary buildings should consider employing this sustainable green roof to achieve thermal comfort environment.